Evaluation of the Sanitary Quality of Sales Channels and Transport Equipment for Frozen Poultry Meat Imported Into Benin - Emmanuella G. H. A. Ganiero; Loglohoué M. G. Quenum; Ignace Dotche; Chakirath F. A. Salifou; Issaka Youssao Abdou Karim; Simplice Karou (Journal of Food Quality)
Meat is a precious, highly perishable commodity, and its hygienic quality must be a priority. The aim of this study is to assess the sales channels and means of transport for imported frozen poultry meat in Benin. Actors in the distribution chain were surveyed in the communes of Cotonou, Abomey-Calavi, Porto-Novo, Lokossa, Aplahoué, Pobè, and Bohicon. A total of 17 importers, 18 wholesalers, 71 retailers, and 40 consumers were interviewed by questionnaire. Importers were predominantly male (65%), university graduates (65%), and economic operators (53%). The study identified three groups of meat distributors: Group 1 is made up of primary and uneducated distributors, who use cabs and motorcycles to transport meat; Group 2 is made up of secondary and primary school students, who use nonrefrigerated vehicles; and Group 3 is made up of secondary and tertiary school vendors, who use refrigerated trucks. Voluntary and involuntary power cuts on the one hand, and packaging problems on the other, lead to storage problems for these meats, resulting in putrefied meat. In addition, 62.5% and 11.7% of importers reexport meat to Nigeria and Niger, respectively, without respecting the cold chain. Analysis of the distribution chain revealed that improper handling of these frozen meats exposes them to bacterial contamination.